2023
DOI: 10.3390/v15020376
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Approach for Detection of Ovine Small Ruminant Retrovirus Co-Infections

Abstract: Jaagsiekte retrovirus (JSRV)-induced ovine pulmonary adenocarcinoma (OPA) is an important ovine respiratory disease in Switzerland. Furthermore, ovine lungs with OPA frequently exhibited lesions suggestive of maedi-visna virus (MVV) or caprine arthritis encephalitis virus (CAEV) infection, indicating that co-morbidities might occur. Lungs and pulmonary lymph nodes were sampled from suspected OPA cases, inflammatory lung lesions and control lungs (total of 110 cases). Tissues were (a) processed for histology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Due to the identical envelope glycoproteins, JSRV and Enzootic Nasal Tumor Virus (ENTV) of sheep and goat nasal adenocarcinomas can cause cell transformation and malignancy (Monot et al 2015). The occurrence of co-morbidities has been suggested by the frequent reports of JSRV-induced OPA in sheep flocks together with MVV and CAEV in recent years (Rosato et al 2023). In a similar study in India, MVV, JSRV, and mycoplasma co-infection were reported in sheep and goats (Valecha et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the identical envelope glycoproteins, JSRV and Enzootic Nasal Tumor Virus (ENTV) of sheep and goat nasal adenocarcinomas can cause cell transformation and malignancy (Monot et al 2015). The occurrence of co-morbidities has been suggested by the frequent reports of JSRV-induced OPA in sheep flocks together with MVV and CAEV in recent years (Rosato et al 2023). In a similar study in India, MVV, JSRV, and mycoplasma co-infection were reported in sheep and goats (Valecha et al 2023).…”
Section: Introductionmentioning
confidence: 99%